Implementation of Social Security for Workers in the Transportation Sector in Banjarnegara Regency - Shaidah, Zahra Az; Martitah, Martitah (TRUNOJOYO LAW REVIEW, 2025)
This study aims to analyse the implementation of social security for workers in the transportation sector in Banjarnegara Regency and identify obstacles in its implementation. The study's contribution lies in strengthening the literature on social protection for informal workers who are at high risk but have minimal protection. The research method employed in this study is a qualitative approach, utilising empirical legal research techniques through interviews, observations, and document studies. The study's results indicate that the level of worker participation remains low due to limited legal literacy, economic constraints, and inadequate supervision. Complicated registration and claim procedures are also major obstacles. The study's conclusion confirms that the program has not been running optimally, despite already having a strong legal basis. Recommendations submitted include increasing education, simplifying procedures, subsidising contributions, and strengthening synergy between agencies and worker communities. These efforts are important to realise fair and equitable work protection in the regions.